ANALYSING DISCOURSE MARKERS IN POPULAR YOUTUBE VIDEOS - Mulia Wikan Subekti; Ariany Restu Kurnia Santi (Faculty of Education and Teachers Training, 2019)
English language learning process of EFL learners is frequently evaluated through their performance in using the language, in particular their speaking performance. However, achieving spoken fluency is not an easy task for those learners due to many constraints ranging from linguistic aspects to personal aspects. Speaking is particularly complicated as it involves simultaneous processes: articulating and thinking process, and hence quite often people use typical words knows as Discourse Markers (DMs) to mediate the thinking process before they actually articulate ideas in their minds. In most occasions DMs are not explicitly taught in the EFL classroom; however, due to the advancement of technology, EFL learners can acquire them from their independent learning mainly through accessing English YouTube channels. In response to that, this paper examines DMs used in some popular YouTube videos, selected based on the number of their subscribers. The data which were in the form of words/phrases derived from the utterances contained in the videos were analysed qualitatively using Fraser’s DMs construct (1991). The results indicated that DMs in the form of Discourse Activity markers functioning as clarifying occurred the most throughout the videos, represented by the use of DMs like (occurred 68 times), just (56 times), and really (36 times). Next trends, in sequence, were DMs in the form of Message Relationship markers functioning as presenting parallels and elaboration, represented by the use of DMs and which occurred 105 times.